Scouts' and educational stakeholders' perceptions of integrating scouting methods into formal education - Zsuzsanna Dégi; Anita Asztalos (Debrecen University Press, 2021)
Scouting is a non-formal learning environment which implies a form of learning that is "less organised than formal learning, but still consists of planned activities and educational objectives. It is also seen as being more concerned with action, and learning by doing from experience; and more holistic, with a particular focus on developing social and emotional skills" (Bridwell et.al., 2015: 27). The Scouting Method used relies on the concept of experiential learning or learning by doing and combines it with other educational elements such as the symbolic framework, team or patrol system, gamification elements such as the badge system (Christians 2018) and active learning or personal progression so that each young person is "consciously and actively involved in his or her own development" (WOSM 1998: 47). The present paper aims to explore scouts' and educational stakeholders' (teachers and scout teachers) beliefs and opinions regarding scouting methods and the way these methods could be integrated into the formal learning environment. Qualitative and quantitative methods of analyses were used to examine and interpret the results gathered through an online questionnaire. Results show that all respondents have a positive attitude towards scouting and the methods used within their activities and they would encourage others to join the association. Even school subjects have been identified which could serve as bridging points between non-formal and formal educational situations.